Deviation in tuning of optical properties of polycrystalline AgSeTe thin films. Issue 186 (2nd January 2018) - Chaudhary, Neeru; Tripathi, S. K.; Goyal, Navdeep
ABSTRACT: The semiconductor alloys of Selenium, Tellurium doped with metals are extensively studied for their optical properties and electrical transport phenomena. This work reports the optical constants of Silver doped Selenium Telluride thermally evaporated two dimensional structures. The optical energy gap calculated from the Tauc plots follows drop to a certain doping level, and then follow the deviation in the trend. Similar deviation is observed in the refractive index, dielectric constants and absorption coefficient in the studied compositions. Conventional method of Swanepoel is used to find the optical coefficients. The trend is explained using the concepts of mean coordination number, electronegativity, chemical bond approach and cohesive energy approach.